FACTORS AFFECTING HUMAN RESOURCE PRACTICES IN A SAMPLE OF DIVERSIFIED JORDANIAN ORGANIZATIONS - Dirar Abdelaziz attallah AL-maaitah, Tamara AL- Maaitah, Dr.Abdullah Al-shourah (International Journal of Research Science and Management, 2015)
This study aimed at studying the factors that affect HR practices in some Jordanian organizations. The factors in this paper include firm size (No. of employees), sector (whether government, private or non-government organization), and profitability (profit Vs non-profit organization). A stratified random sample of 70 establishments that employ more than 50 employees was selected to cover government, private and non-government sectors.